Perancangan Sistem Informasi Monitoring Perjalanan Dinas Pegawai Badan Pusat Statistik Kabupaten Malang Berbasis Web Menggunakan API Google Calendar - Novia Herdiandini; Widhy Hayuhardhika Nugraha Putra; Buce Trias Hanggara (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
The Central Statistics Agency of Malang Regency is a government agency that collects statistical data in Malang Regency through a census. This census activity is called outstation activity. Each employee must report the outstation activity to the Administrative Sub-Staff so that presence doesn't marked as absence. However, in its implementation, there were a constrain that all employee were reporting via WhatsApp chat. While, recording the data by entering the data into Microsoft Office Excel. Either data is recapitulated by creating a calendar of outstation activity markers in Microsoft Office Excel. Based on that problem, it is necessary to build Outstation Activity Monitoring Information System. This is a web-based system so that employee can reported the data easily. This system is also integrated with the Google Calendar API so that it can show data in form of calendar which make it easier for outstation activity. The results of this study consist of 13 functional requirements that can be traced 13 use cases, 13 activity diagrams, 13 sequence diagrams and 15 interface design. The system is tested using the Traceability Matrix and the result show valid requirement and design document. While testing the prototype, the results of the system design were in accordance with what was expected by the employees and the Administrative Sub-Staff.